ACCESSION OF LOTS: ACCESSIO PER ARTES MAGICAS? Pocock v De Oliviera 2007 2 SA 90 (W) - PJ Badenhorst; JM Pienaar (Obiter, 2022)
One of the challenges of being a property law teacher is marking the script of a student who has “spotted” accession for the exam, but answers a question dealing with restrictive conditions by writing shotgun-style everything he or she knows about accession. The same feeling is experienced when one reads the above decision. The only difference is the absence of students in this case.